2018
DOI: 10.26717/bjstr.2018.04.0001002
|View full text |Cite
|
Sign up to set email alerts
|

Candida sp. As a Potential Reservoir and Transmission Facilitator of Helicobacter Pylori

Abstract: Helicobacter pylori is a bacterium broadly distributed in the world, colonizing nearly 50% of the human population. Its niche is the human stomach, where it is able to generate several gastric pathologies. A numbers of studies have detected Candida sp. together with H. pylori in the stomach, condition which could increase the severity of the gastric damage. Nevertheless, the association between these two microorganisms is closer because it has been reported that H. pylori can be found active within vacuoles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Biofilm provides a self-protective matrix that can make the bacteria up to 1000 times more resistant to antibiotics, and this mechanism could also potentially contribute to the failure of H. pylori eradication efforts [ 16 ]. Furthermore, it has recently been shown that H. pylori behaves as a facultative intracellular bacterium, found inside eukaryotic cells including human gastric epithelial cells, and macrophages and dendritic immune cells [ 17 , 18 ]. Interestingly, the presence of H. pylori inside the Candida yeasts’ vacuoles has been confirmed recently by fluorescence microscopy and H. pylori -specific genes and proteins have been isolated from the yeast cells [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Biofilm provides a self-protective matrix that can make the bacteria up to 1000 times more resistant to antibiotics, and this mechanism could also potentially contribute to the failure of H. pylori eradication efforts [ 16 ]. Furthermore, it has recently been shown that H. pylori behaves as a facultative intracellular bacterium, found inside eukaryotic cells including human gastric epithelial cells, and macrophages and dendritic immune cells [ 17 , 18 ]. Interestingly, the presence of H. pylori inside the Candida yeasts’ vacuoles has been confirmed recently by fluorescence microscopy and H. pylori -specific genes and proteins have been isolated from the yeast cells [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has recently been shown that H. pylori behaves as a facultative intracellular bacterium, found inside eukaryotic cells including human gastric epithelial cells, and macrophages and dendritic immune cells [ 17 , 18 ]. Interestingly, the presence of H. pylori inside the Candida yeasts’ vacuoles has been confirmed recently by fluorescence microscopy and H. pylori -specific genes and proteins have been isolated from the yeast cells [ 17 , 18 , 19 , 20 ]. Internalization of the H. pylori inside the Candida yeast cells has been characterized as a protective adaptation to stressful conditions, including changes in pH values, antibiotics treatments, and nutrient-deficient environment [ 16 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations